Efficient laser operation of Nd3+:Lu2O3 at various wavelengths between 917 nm and 1463 nm. (15th June 2016) - von Brunn, P; Heuer, A M; Fornasiero, L; Huber, G; Kränkel, C
Abstract: Even though the first Nd 3+ -doped sesquioxide lasers have been realized more than 50 years ago, up to now no reports on efficient laser operation of Nd 3+ :doped sesquioxides can be found. In this work, we review the favorable spectroscopic properties of the sesquioxide Nd 3+ :Lu2 O3 in terms of ground state absorption, stimulated emission, and excited state absorption cross sections as well as the upper level lifetime. Making use of these properties, we achieved efficient laser performance on eight different laser transitions in the wavelength range between 917 nm and 1463 nm under Ti:sapphire laser pumping using state-of-the-art HEM-grown Nd 3+ :Lu2 O3 crystals with good optical quality. At the strongest transition around 1076 nm we determined a slope efficiency of 69%, which represents the highest efficiency ever obtained for a Nd 3+ -doped sesquioxide. Furthermore, we could generate watt level output powers and high slope efficiencies for seven other transitions. Lasers at 917 nm, 1053 nm, 1108 nm and 1463 nm were realized for the first time and the latter represents one of the longest laser wavelengths obtained on the 4 F3/2   →   4 I13/2 transition in Nd 3+ -doped materials.